Preserving the Existence of Sea Turtles: The Government Policies and Roles on Conservations - Utama, Gwendolyn Ingrid; Pangesti, Shinta; Vatresia, Laura Cindy (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
Sea turtles are reptiles that live in the sea which have long been threatened, both from nature and human activities. Internationally, sea turtles are included in the 'red list' in the International Union for Conservation of Nature's (IUCN) and Appendix I of the Convention on International Trade in Endangered Species of Wild Flora and Fauna (CITES), which means that their existence in nature is threatened with extinction so that all the form of utilization and distribution must receive serious attention. Therefore, sea turtle conservation efforts are an important program to protect and save the populations, especially in Indonesia because there are 6 out of 7 sea turtles species still exist today in Indonesia. In order to support sea turtle conservation efforts in Indonesia, government roles are needed, both at the central and regional levels. This research focuses on the preserving sea turtles based in Indonesia through government policies and roles regarding conservations at Serangan Island and Tanjung Benoa, especially local government. The purpose of this research was to analyze government policies and their roles on sea turtle conservation efforts at Serangan Island and Tanjung Benoa. The research method used is normative using secondary data supported by primary data in the form of interviews with the management of the conservation centers. The research result shows that central government regulations are not always passed down to the regional level, but the government's awareness to protect the existence of turtles has been carried out together with the society even without regional regulations.